Burke’s “Revolutionary Book”: Conservative Politics and Revolutionary Aesthetics in the Reflections - Castellano, Katey (Romanticism on the Net, 2007)
AbstractThis essay explores the seemingly disjointed relationship between politics and aesthetics in Burke’s Reflections on the Revolution in France (1790), questioning why the first articulation of conservative traditionalism would be announced in a shockingly new, experimental style. One of Novalis’s aphorisms suggests that Burke’s Reflections inverts common assumptions about the relationship between politics and aesthetics: “Many antirevolutionary books have been written for the Revolution. But Burke has written a revolutionary book against the Revolution.” As Novalis observed, Burke’s Reflections defies the formal conventions of political prose; Burke outlines his defense of traditional British institutions in an idiom that approaches the excesses of modernist montage in its patchwork of genres. His unsystematic style juxtaposes and blends, often in seemingly incongruous ways, diverse literary genres and rhetorical forms: the legalistic-latinate idiom, the captivity narrative, the biblical epistle, the political tract, the gothic novel, enthusiastic prophecy, chivalric romance, and tragedy. While these disparate literary forms erupt unpredictably in the Reflections, they do so in a fragmented, at times even grotesque manner, revealing what Burke himself admitted, that his conservative project is premised on an invented tradition devoid of all referential consistency and stability. In the face of an economy that was changing the very nature of value as such, Burke aesthetically revives fragments of tradition from the past and arranges them in an anti-utilitarian way that might conserve what he understood to be their pre-capitalist, non-relative value.